Studi Kelayakan Penentuan Lokasi Tempat Pengolahan Sampah Terpadu (TPST): Studi Kasus Desa Nanga Kecamatan Wawonii Timur Kabupaten Konawe Kepulauan - Hamid, Arifudin; Srikandi, Eka Dian; Ndibale, Wa (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Nanga village is a village located in East Wawonii District which is still said lagging city. There has no effective waste disposal site, and several communities choose to throw garbage into the ocean directly and the river. So that, it can be collected and managed properly and efficiently garbage by using the planning design of an integrated waste processing site (TPST) location to handle and reduce the negative impacts of garbage. The research variable refers to regional, allowance, and placement eligibilities (SNI 03-3241-1994). Based on this research, we discover the Nanga village stated in the medium classification to develop an integrated waste processing site in East Wawonii District.